CONTINUOUS RECORDING OF CHLOROPHYLL A WITH A MOORED BUOY SYSTEM IN BREID BAY, ANTARCTICA, DECEMBER 1985-FEBRUARY 1986 - フクチ, ミツオ; ハツトリ, ヒロシ; FUKUCHI, Mitsuo; HATTORI, Hiroshi (National Institute of Polar Research, 1988)
P(論文) departmental bulletin paper